Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan dengan Profitabilitas dan Free Cash Flow Sebagai Pemoderasi - Mahendra, I Made Adi; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 24 No 3 (2018), 2018)
Every company will strive to increase the value of the company through increasing the prosperity of the owner or shareholders by improving the company's performance. Increased corporate performance one of which can be done by applying social responsibility (CSR). This study aims to test and obtain empirical evidence of the influence of Corporate Social Responsibility (CSR) on the value of companies with profitability and free cash flow as a moderator. This research was conducted at mining company listed in Bursa Efek Indonesia (BEI) year 2013-2016. Sampling method used is purposive sampling. The number of samples meeting the criteria is 10 companies. Methods of data collection is done by documentation method. Data analysis technique used is Moderated Regression Analysis (MRA). The result of moderation testing between Corporate Social Responsibility and corporate value shows a positive influence which means profitability and free cash flow strengthens the influence of Corporate Social Responsibility towards firm value. Keywords : firm value, CSR, profitability, free cash flow